Regional differences and spatio-temporal convergence of environmental regulation efficiency in the Yellow River Basin, China - Lu, Fei; Ren, Huaiguo; Zhai, Xinglong (Frontiers in Ecology and Evolution, 2023)
Environmental regulation efficiency facilitates environmental governance performance assessment, ecological protection, and high-quality development. Herein, based on the panel data of 75 cities in the Yellow River Basin from 2007 to 2020, this paper constructed an evaluation index system and measured the environmental regulation efficiency using a super-EBM hybrid distance model. We analyzed the regional differences and dynamic evolution characteristics of environmental regulation efficiency with the help of Dagum’s Gini coefficient decomposition and kernel density estimation methods. Furthermore, a spatial econometric model explored the spatio-temporal convergence of environmental regulation efficiency. The main findings show that the environmental regulation efficiency of the overall Yellow River Basin and the upper, middle, and lower reaches showed an increasing trend with significant within-region spatial differences. The differences between all regions had a narrowing trend. The primary source of spatial differences in environmental regulation efficiency was the intensity of transvariation. The dynamic evolution characteristics of environmental regulation efficiency in different regions were quite different, and the spatial polarization phenomenon was more evident in the upper reaches. Except for the overall Yellow River Basin, all regions existed σ convergence. The results of spatial convergence estimation indicated absolute and conditional β convergence in all regions. The findings provide a factual reference for policies related to establishing policy systems for environmental regulation efficiency and green coordinated development in similar regions of the world.